IMPLEMENTATION OF ROAD MAINTENANCE PROGRAM AT THE PUBLIC WORKS OFFICE IN SUKABUMI REGENCY - Fachry Muchamad Daradjat; M. Rijal Amirulloh; Rizki Hegia Sampurna (DIA: Jurnal Administrasi Publik, 2023)
The road maintenance program is a series of tasks completed in order to maintain or fix current facilities so that they adhere to standards (according to functional and quality standards). When there is structural damage to the road, normal and periodic maintenance on the roads is the only thing that needs to be done. This study intends to ascertain how the Sukabumi Regency Public Works Service has implemented the Road Maintenance Program. the mthode uses a descriptive qualitative approach. Observation, interviews, and documentation are all forms of data collecting. The four program implementation dimensions from Edward III are used in this study. Based on the resource dimension, which comprises human resources and budgetary resources, the study's findings show that the Public Works Service's implementation of the road repair program in Sukabumi Regency is not ideal. As soon as it is clear from the communication, disposition, and political structure aspects that things are going well.